La compasión como virtud moral y política desde la teoría de las emociones de Martha Nussbaum. Reflexiones sobre la obra Paisajes del pensamiento. La inteligencia de las emociones - Cáceres Frisancho, Silvia Juanita (2022)
The main objective of this paper is to show that compassion is a moral and political virtue capable of contributing to ethical deliberation in both the private and public spheres. To carry out this task, the starting point will be the theory of emotions and the cognitive, evaluative and eudaimonistic interpretation of compassion that Martha Nussbaum develops, based on Aristotle, mainly in her work Upheavals of Thought. The Intelligence of Emotions. Nussbaum's theory allows us to affirm that emotions play an active role in people's reasoning, when they deliberate, weigh reasons and determine courses of action; therefore, the emotions cannot be excluded from ethical deliberation. Likewise, from the critical approach made by contemporary authors such as John Deigh, Michael Weber, Roger Crisp and Marta Gil to Nussbaum's approaches, the concept of this author will be specified and nurtured, affirming that compassion is above all a virtue that incorporates a sense of justice and an eudaimonistic dimension that allows it to contribute positively to the ethical reasoning of people. On this basis and taking into account the objections that the Stoic tradition raises to this emotion, we will evaluate to what extent this emotion is rational in a normative sense and what its contributions to ethical deliberation in the public sphere could be. On the basis of Nussbaum's proposals and defense of compassion, it will be pointed out that this nourishes with a vital content those principles and norms that govern a liberal democracy, where public institutions and civil society take on special relevance by providing the necessary mechanisms so that the possible contributions of this emotion and virtue can be effective.